The leadership investment : how the world's best organizations gain strategic advantage through leadership development - Fulmer, Robert M.; Goldsmith, Marshall (New York : AMACOM, 2001)
"In The Leadership Investment, six of today's top organizations pull back the curtains to offer a revealing look into their own leadership development programs - programs that, dollar for dollar, repeatedly justify their costs. Based on an innovative, in-depth study of leadership development programs worldwide, this book offers concrete examples of how these organizations are using leadership development to consistently advance their strategic objectives."--Jacket
Introduction : leadership development lessons from the best -- The competitive advantage of leadership development -- Arthur Andersen : the search for qualification -- General Electric : staging ground for corporate revolution -- Hewlett-Packard : diversity and development through decentralization -- Johnson & Johnson : frameworks of leadership -- Royal Dutch Shell : LEAP to remain a living company -- The World Bank : its most important investment -- Corporate universities : a source of competitive advantage -- Saturn as model -- Universities : learning to listen -- Leadership development firms : new faces of competition -- The strategic challenge -- List of abbreviations.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Executives -- Training of -- Case studies; Leadership -- Study and teaching -- Case studies; Leadership -- Étude et enseignement -- Études de cas; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; Executives -- Training of; Leadership -- Study and teaching; Case studies